Bridging the Cervicothoracic Junction During Multi-Level Posterior Cervical Decompression and Fusion: A Systematic Review and Meta-Analysis. Issue 1 (January 2023) - Truumees, Eeric; Singh, Devender; Ennis, Darlene; Livingston, Heather; Duncan, Ashley; Lavelle, William; Riesenburger, Ron; Yu, Anthony; Geck, Matthew; Mroz, Thomas; Stokes, John
Study Design: Systematic review and Meta-analysis. Objective: This systematic review seeks to compare fusion, reoperation and complication rates, estimated blood loss (EBL), and surgical time between multi-level instrumented fusions with LIVs (lowest instrumented vertebra) in the cervical spine and those that extend into the thoracic spine. Summary of Background Data: Several studies address the question of whether to extend a long-segment, posterior cervical fusions, performed for degenerative disease, into the upper thoracic spine. Recommendations for appropriate LIV continue to vary. Methods: A comprehensive computerized literature search through multiple electronic databases without date limits up until April 3rd, 2020 using combinations of key search terms and sets of inclusion/exclusion criteria was performed. Results: Our comprehensive literature search yielded 3852 studies. Of these, 8 articles consisting of 1162 patients were included in the meta-analysis. In 61.2% of the patients, the fusion did not cross the cervicothoracic junction (CTJ) (cervical LIV, CLV). In the remaining 38.8%, the fusion extended into the upper thoracic spine (thoracic LIV, TLV). Overall, mean patient age was 62.5 years (range: 58.8-66.1 years). Our direct analysis showed that odds of fusion were not statistically different between the CLV and TLV groups (OR: .648, 95% CI: .336-1.252, P = .197). Similarly, odds of reoperation (OR: 0.726, 95% CI: 0.493-1.068, P = .104) and complication rates were similar between the 2 groups (OR: 1.214, 95% CI: 0.0.750-1.965, P = .430). Standardized mean difference (SMD) for the blood loss (SMD: .728, 95% CI: 0.554-.901, P = .000) and operative (SMD: 0.653, 95% CI: .479-.826, P = .000) differed significantly between the 2 groups. The indirect analysis showed similar fusion (Effect Size (ES)TLV : .892, 95% CI: .840-.928 vs ESCLV :0.894, 95% CI:0.849-.926); reoperation rate (ESTLV :0.112, 95% CI: 0.075-.164 vs ESCLV : .125, 95% CI: .071-.211) and complication rates (ESTLV : .108, 95% CI: .074-.154 vs ESCLV :0.081, 95% CI: .040-.156). Conclusions: Our meta-analysis showed that fusion, complication, and reoperation rates did not differ significantly between patients in whom multi-level posterior fusions ended in the cervical spine vs those of which was extended into the thoracic spine. The mean blood loss, operative time and length of stay were significantly lower in patients with CLV at C6 or C7, compared to their counterparts. These data suggest that, absent focal, C7-T1 pathology, extension of long, posterior cervical fusions into the thoracic spine may not be necessary.